2014
DOI: 10.1016/j.bbadis.2014.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin G activity lowers plasma LDL and reduces atherosclerosis

Abstract: Cathepsin G (CatG), a serine protease present in mast cells and neutrophils, can produce angiotensin-II (Ang-II) and degrade elastin. Here we demonstrate increased CatG expression in smooth muscle cells (SMCs), endothelial cells (ECs), macrophages, and T cells from human atherosclerotic lesions. In low-density lipoprotein (LDL) receptor-deficient (Ldlr−/−) mice, the absence of CatG reduces arterial wall elastin degradation and attenuates early atherosclerosis when mice consume a Western diet for 3 months. When… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 61 publications
1
27
0
Order By: Relevance
“…Recently, it was established that chymase cleaves ApoA-I resulting in loss of its anti-inflammatory functions [20]. Moreover, cathepsin G, another protease released from mast cells, has been reported to degrade LDL, reducing LDL-C and ApoB levels [21]. Excessive mast cell protease activity in SM patients may be, at least in part, responsible for the altered apolipoprotein profile observed.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was established that chymase cleaves ApoA-I resulting in loss of its anti-inflammatory functions [20]. Moreover, cathepsin G, another protease released from mast cells, has been reported to degrade LDL, reducing LDL-C and ApoB levels [21]. Excessive mast cell protease activity in SM patients may be, at least in part, responsible for the altered apolipoprotein profile observed.…”
Section: Discussionmentioning
confidence: 99%
“…3032 Although little contribution of CatG has been described in the microcirculation in terms of leukocyte recruitment, several studies have pointed toward its potential importance in inflammation in large vessels. 3335 This could denote a tissue-specific relevance of these proteases, where CatG assists myeloid cells to adhere to inflamed arteries, whereas neutrophil elastase controls microvascular recruitment. Interestingly, we found that the effect of CatG is independent of its proteolytic activity, but could be abrogated with an antibody.…”
Section: Discussionmentioning
confidence: 99%
“…However, MC are not the only source of the enzyme, it is also released from activated neutrophils and macrophages [8][9][10]. Despite that cathepsin G may promote early atherogenesis as it is an elastase [11] and collagenase activator [12], Wang et al [13] suggested that cathepsin G promotes early atherogenesis through its elastinolytic activity, but at the same time suppresses late progression of atherosclerosis. In their study, patients with atherosclerosis had significantly reduced plasma levels of cathepsin G that were in negative correlation with total cholesterol and low density lipoprotein (LDL), but not high density lipoprotein (HDL) or triglycerides, suggesting a role of cathepsin G in degradation of LDL without affecting HDL or triglycerides [13].…”
Section: łUkasz Lewicki Et Al Mast Cells In Coronary Artery Diseasementioning
confidence: 99%